Sorghum Tempeh on Cholesterol Levels and Histopathology of Aorta in High-Fat Diet-Induced Rat Model - Bintang, Francisca Natalia; Lestari, Endang Sri; Afifah, Diana Nur; Muniroh, Muflihatul; Anjani, Gemala; Syauqy, Ahmad; Djamiatun, Kis (Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Elevated cholesterol levels are associated with hypercholesterolemia, the primary cause of death and lost productivity, and a significant risk factor for the onset of cardiovascular disease. Sorghum is known for its high bioactive components and phenolic compounds, flavonoids, β-glucans, and dietary fiber, which act as anti-cholesterol properties.Objective: This study aimed to analyze the impact of sorghum tempeh on cholesterol levels and histopathology of aorta in rats fed a high-fat diet.Methods: A total of 24 male 8-weeks-old Sprague Dawley rats were randomly assigned to four groups: standard diet group (SD), high-fat diet control group (FD), rats fed high-fat diet + low dose of sorghum tempeh (T1), and high-fat diet + high dose of sorghum tempeh (T2). Measurements of cholesterol levels were determined using the total cholesterol ELISA method. Histopathology of aorta analysis was carried out after four weeks of intervention of the four treatment groups using Hematoxylin-Eosin staining.Results: The average total cholesterol levels post-intervention in the SD, FD, T1, and T2 were 89.986±2.089, 220.365±3.847, 121.161±4.111, and 97.836±2.504 mg/dL, respectively. The results showed that the total cholesterol level significantly decreased (p<0.05) after giving a formula of sorghum tempeh with doses of 0.75 g and 1.50 g per 200 g body weight of rats for four continuous weeks. Histopathology of the aorta in the FD and T2 groups showed a significant difference compared to the SD group. The result which was closest to the SD group was the T1 group.Conclusion: Sorghum tempeh is a high-fiber and antioxidant source that can control hypercholesterolemia by lowering serum total cholesterol. It is also possible to improve histopathology but not yet able to approach normal conditions. The administration of sorghum tempeh with a low dose is sufficient, and further research is still required to determine the effect of sorghum tempeh on aorta histopathology.